Fitness costs of Tn1546-type transposons harboring the vanA operon by plasmid type and structural diversity in Enterococcus faecium - Dokyun Kim; Da Young Kang; Min Hyuk Choi; Jun Sung Hong; Hyun Soo Kim; Young Ree Kim; Young Ah Kim; Young Uh; Kyeong Seob Shin; Jeong Hwan Shin; Soo Hyun Kim; Jong Hee Shin; et al. (BMC, 2024)
Abstract Background This study analyzed the genetic traits and fitness costs of vancomycin-resistant Enterococcus faecium (VREfm) blood isolates carrying Tn1546-type transposons harboring the vanA operon. Methods All E. faecium blood isolates were collected from eight general hospitals in South Korea during one-year study period. Antimicrobial susceptibility testing and vanA and vanB PCR were performed. Growth rates of E. faecium isolates were determined. The vanA-positive isolates were subjected to whole genome sequencing and conjugation experiments. Results Among 308 E. faecium isolates, 132 (42.9%) were positive for vanA. All Tn1546-type transposons harboring the vanA operon located on the plasmids, but on the chromosome in seven isolates. The plasmids harboring the vanA operon were grouped into four types; two types of circular, nonconjugative plasmids (Type A, n = 50; Type B, n = 46), and two types of putative linear, conjugative plasmids (Type C, n = 16; Type D, n = 5). Growth rates of vanA-positive E. faecium isolates were significantly lower than those of vanA-negative isolates (P < 0.001), and reduction in growth rate under vancomycin pressure was significantly larger in isolates harboring putative linear plasmids than in those harboring circular plasmids (P = 0.020). Conclusions The possession of vanA operon was costly to bacterial hosts in antimicrobial-free environment, which provide evidence for the importance of reducing vancomycin pressure for prevention of VREfm dissemination. Fitness burden to bacterial hosts was varied by type and size of the vanA operon-harboring plasmid.